Imaging the invisible—Bioorthogonal Raman probes for imaging of cells and tissues - Matanfack, Georgette Azemtsop; Rueger, Jan; Stiebing, Clara; Schmitt, Michael; Popp, Jürgen (Journal of Biophotonics, 2020)
A revolutionary avenue for vibrational imaging with super-multiplexing capability can be seen in the recent development of Raman-active bioortogonal tags or labels. These tags and isotopic labels represent groups of chemically inert and small modifications, which can be introduced to any biomolecule of interest and then supplied to single cells or entire organisms. Recent developments in the field of spontaneous Raman spectroscopy and stimulated Raman spectroscopy in combination with targeted imaging of biomolecules within living systems are the main focus of this review. After having introduced common strategies for bioorthogonal labeling, we present applications thereof for profiling of resistance patterns in bacterial cells, investigations of pharmaceutical drug-cell interactions in eukaryotic cells and cancer diagnosis in whole tissue samples. Ultimately, this approach proves to be a flexible and robust tool for in vivo imaging on several length scales and provides comparable information as fluorescence-based imaging without the need of bulky fluorescent tags.
CRIS-Team Scopus Importer:2023-04-20
Keywords: bacteria; eukaryotic cells; multiplexing; Raman spectroscopy; Raman tags; SRS; stable isotope labeling; tissues